KADAR DAN KOMPOSISI KIMIA MINYAK PADA BAGIAN-BAGIAN BUAH KELAPA SAWIT (Elaeis guineensis Jacq.) DARI DELAPAN VARIETAS PPKS - Sujadi Sujadi; Hasrul Abdi Hasibuan; Meta Rivani; Abdul Razak Purba (Jurnal Penelitian Kelapa Sawit, 2016)
Fresh fruit bunches (FFB) consist of fruit be composed grade in few spikelet. Fruit at a spikelet can be distinguished into performed fruit namely internal fruit, middle fruit and outer fruit as soon as each section contain parthenocarpy fruits. This research was conducted for determine composition and content fatty acid of oil at internal fruit, middle, outer and parthenocarpy fruit from oil palm fruit. Samples of fruit came from 3 – 5 spikelet the central of FFB. Result showed that oil content of outer fruit (46.9 + 9.9)% trend higher be compared middle fruit (42.8 + 10.3)% and internal fruit (39.1 + 9.5)%. Parthenocarpy fruits have a low oil content (14.2 + 16.2)% except yellowish fruit trend high relatively oil content. The main components of fatty acid at outer fruit, middle and internal are palmitic acid, oleic, linoleic and stearic with mean value respectively (44.8 – 45.8)%, (37.6 – 38.0)%, (9.9 – 10.9)% and (4.6 – 4.8)%. Oil content at parthenocarpy fruit have amount main component of fatty acid with performed fruit but composition of palmitic acid (40.0 + 5.9)% and oleic (34.6 + 8.4)% lower while linoleic acid (16.9 + 8.5)% and linolenic (1.6 + 1.8)% higher be compared to performed fruit. Simalungun variety has the highest oil content in the part of fruit, with that PPKS 540 and La Mé respectively. PPKS 540 variety has the highest oleic acid content while PPKS 718 has the highest linoleic content.